Protective Immune Response of Post Rabies Vaccinated Dogs in Buduk Village, Mengwi, Badung, Bali (RESPONS IMUN PROTEKTIF PADA ANJING PASCAVAKSINASI RABIES DI DESA BUDUK, MENGWI, BADUNG, BALI) - Suardana, Ida Bagus Kade; Winaya, Ida Bagus Oka; Dewi, Desak Wiga Puspita; Sudarmayasa, I Wayan; Agustina, Kadek Karang (Jurnal Veteriner; Vol 20 No 2 (2019)DO - 10.19087/jveteriner.2019.20.2.264, 2019)
In efforts to eradicate rabies disease, vaccinations have been carried out targeting so-called rabies carrier animal such as dog andcat. Mass rabies vaccination has been done by the government of Bali annualy, in every sub-village at vaccination post or at every household.  Minimum vaccination coverage to protect the threatened dog population from rabies is 70%. To determine whether the vaccinated dogs have protective antibody against rabies, this study have been done to find out the immune response of dogs after rabies vaccination in Buduk village. Sera were collected using random sampling in each subvillage, a total of 30 serum sample were examined, and the antibody was tested using kit ELISA Rabies®. Elisa test resulted in 90% of dogs have protective antibody titers (OD>0.5 EU). It concluded that dogs in Buduk village have a good immune response against rabies vaccine.